Design and Analysis of New Prosthetic Foot. - Jweeg, Muhsin J.; Al-Beiruti, Ahamed A.; Al-Kinani, Kadhim K. (Al-Khwarizmi Engineering Journal, 2007)
There is a variety of artificial foot designs variable for use with prosthetic legs . Most of the design can be divided into two classes, articulated and non-articulated feet. one common non-articulated foot is the SACH . The solid ankle cushion heel foot referred to as the SACH foot has a rigid keel . One key or the key factor in designing a new prosthesis is in the analysis of a patients response . This view is the most important because if the foot does not provide functional , practical or cosmetically acceptable characteristics the patient will not feel comfortable with the prosthesis , therefore design and manufacturing a new foot is essential, this foot made from polyethylene, its different shape and characteristics The characteristics deemed important by patients in achieving natural gait motion include: Dorsiflexion Energy return Fatigue test In this study, including all these characteristics test, design fatigue foot tester according to ISO 10328 and design new foot .Also, the testometric crosshead was modified to find dorsiflexion angle and energy return .The fatigue criteria for polymer was proposed, in mathematical solution. Finally , the characteristics of SACH foot was compared with new foot by mathematical solution and used visual basic program and experimental method by different tests. From these test that the new foot is better than SACH foot for all test .